2017
DOI: 10.21273/hortsci12437-17
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Nutrient Concentration Ranges of ‘Hass’ Avocado Cauliflower Stage Inflorescences—Potential Diagnostic Tool to Optimize Tree Nutrient Status and Increase Yield

Abstract: Optimizing ‘Hass’ avocado (Persea americana Mill.) tree nutrient status is essential for maximizing productivity. Leaf nutrient analysis is used to guide avocado fertilization to maintain tree nutrition. The goal of this research was to identify a ‘Hass’ avocado tissue with nutrient concentrations predictive of yields greater than 40 kg of fruit per tree. This threshold was specified to assist the California avocado industry to increase yields to ≈11,200 kg·ha−1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…These results question the pertinence of current nutritional guidelines or leaf mineral nutrient norms that are used for 'Nadorcott' mandarin orchards in an alternate bearing cycle in South Africa, where the purpose of fertilization should be different during an ''on'' vs. an ''off'' season in terms of manipulating vegetative shoot flush, flowering, and fruit load (Stander et al, 2018). Similar to what has been reported for avocado (Persea americana) (Campisi-Pinto et al, 2017), it could be possible that leaf analysis is not sensitive enough to detect changes in macronutrient status of 'Nadorcott' mandarin trees, or differences in fertilization rates that may affect fruit load or result in the manifestation of alternate bearing. For example, in other evergreen fruit trees such as avocado, coffee (Coffea arabica), and olive (Olea europaea), organs such as flowers, petioles of leaves, and stems of flowers and fruit are alternative tree organs from which nutrient analyses provide valuable supplemental information to leaf nutrient analyses (Campisi-Pinto et al, 2017;Castillo-Gonzalez et al, 2000;Khelil et al, 2010;Martinez et al, 2003;Razeto and Salgado, 2004).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…These results question the pertinence of current nutritional guidelines or leaf mineral nutrient norms that are used for 'Nadorcott' mandarin orchards in an alternate bearing cycle in South Africa, where the purpose of fertilization should be different during an ''on'' vs. an ''off'' season in terms of manipulating vegetative shoot flush, flowering, and fruit load (Stander et al, 2018). Similar to what has been reported for avocado (Persea americana) (Campisi-Pinto et al, 2017), it could be possible that leaf analysis is not sensitive enough to detect changes in macronutrient status of 'Nadorcott' mandarin trees, or differences in fertilization rates that may affect fruit load or result in the manifestation of alternate bearing. For example, in other evergreen fruit trees such as avocado, coffee (Coffea arabica), and olive (Olea europaea), organs such as flowers, petioles of leaves, and stems of flowers and fruit are alternative tree organs from which nutrient analyses provide valuable supplemental information to leaf nutrient analyses (Campisi-Pinto et al, 2017;Castillo-Gonzalez et al, 2000;Khelil et al, 2010;Martinez et al, 2003;Razeto and Salgado, 2004).…”
Section: Resultsmentioning
confidence: 67%
“…Similar to what has been reported for avocado (Persea americana) (Campisi-Pinto et al, 2017), it could be possible that leaf analysis is not sensitive enough to detect changes in macronutrient status of 'Nadorcott' mandarin trees, or differences in fertilization rates that may affect fruit load or result in the manifestation of alternate bearing. For example, in other evergreen fruit trees such as avocado, coffee (Coffea arabica), and olive (Olea europaea), organs such as flowers, petioles of leaves, and stems of flowers and fruit are alternative tree organs from which nutrient analyses provide valuable supplemental information to leaf nutrient analyses (Campisi-Pinto et al, 2017;Castillo-Gonzalez et al, 2000;Khelil et al, 2010;Martinez et al, 2003;Razeto and Salgado, 2004). Indeed, studies on mineral nutrients and alternate bearing in other mandarin cultivars, e.g., 'Kinnow' (Mirsoleimani et al, 2014) and 'Michal', 'Wilking', and 'Murcott' (Monselise et al, 1983), have shown that the effects of fruit load in the current season on bud responses in the following season are also closely related to the nutrient concentration in stems.…”
Section: Resultsmentioning
confidence: 70%
“…in fruits that the concentration of the nutrient increases from flowering to early fruit set, and then decreases in fruit growth. Campisi et al (2017), found that P increased as inflorescence development progressed.Additionally, they mention that during the cauliflower phase were found valueshigher than those for full flowering, and the latter even exceeded those found in developing fruits (Campisi et al, 2017). Studies in cowpea obtained similar results regards to the P increase at flowering stage and at the beginning of pod formation (Suzuki et al,2021).…”
Section: Nutritional Dynamics Of Phosphorusmentioning
confidence: 99%
“…The variation of total N remained stable throughout the phenology, like values reported by Figueroa et al (2001). Campisi et al (2017) mentioned that optimal ranges of N in cauliflower inflorescences of 'Hass' vary from 2.7 % to 3 %. In our case, the concentration of 2.7 % was obtained.…”
Section: Nutritional Dynamics Of Total Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation